Candida tropicalis as a promising oleaginous yeast for olive mill wastewater bioconversion - Dias, Bruna (2021)
Olive mill wastewater (OMW), which is generated during olive oil production, has detrimental effects on the environment due to its high organic load and phenolic compounds content. OMW is difficult to biodegrade, but represents a valuable resource of nutrients for microbial growth. In this study, yeast strains were screened for their growth on phenolic compounds usually found in OMW and responsible for antimicrobial effects. Candida tropicalis ATCC 750 demonstrated an extraordinary capacity to grow in phenolics and was chosen for further experiments with OMW-based medium. The effects of nitrogen supplementation, the pH, and the stirring rate on cellular growth, OMW-components consumption, and added-value compounds production were studied in batch cultures in Erlenmeyer flasks and in a bioreactor. Candida tropicalis was able to reduce 68% of the organic load (chemical oxygen demand) and 39% of the total phenols of OMW in optimized conditions in bioreactor experiments, producing lipase (203 U·L−1) and protease (1105 U·L−1). Moreover, intracellular lipids were accumulated, most significantly under nitrogen-limited conditions, which is common in this type of wastewater. The high potential of C. tropicalis to detoxify OMW and produce added-value compounds from it makes this process an alternative approach to other conventional processes of OMW treatment.